2020
DOI: 10.3390/urbansci4040077
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Method for the Estimation of Insertion Loss of Noise Barriers: Comparison with Various Formulae (2D)

Abstract: Noise barriers are a critical part of noise mitigation in urban and rural areas. In this study, a comparison of the insertion loss calculations of noise barriers via the Finite Element Method (FEM) and various formulae (Kurze–Anderson, ISO 9613-2/Tatge, Menounou) is presented in the case of two-dimensional acoustic radiation problems. Some of the cases explored include: receiver in the illuminated zone, in the shadow zone, in the shadow border, source in medium, long, short distance from the barrier, source an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Mathematical methods have been widely used to determine the diffraction properties of the barriers. These methods can be based on the boundary element method [19,20], the finite element method [21,22], and the finite difference method [23].…”
Section: Approaches For Determining Noise Barrier Effectivenessmentioning
confidence: 99%
“…Mathematical methods have been widely used to determine the diffraction properties of the barriers. These methods can be based on the boundary element method [19,20], the finite element method [21,22], and the finite difference method [23].…”
Section: Approaches For Determining Noise Barrier Effectivenessmentioning
confidence: 99%
“…With the development of computer technology, numerical methods for finding sound fields are widely used. In [12,13], the application of the partial element method (FEM) and the boundary element method (BEM) for finding the field around barriers with a specially shaped edge is presented.…”
Section: Research Of Existing Solutions To the Problemmentioning
confidence: 99%
“…Computational methods can be exploited for the study of multi-neck Helmholtz resonators, as previously demonstrated by Selamet et al [34] utilizing a BEM. Among computational methods, the FEM is probably the most widely used in acoustic problems and has been applied for noise control [37], in architectural and environmental acoustics [38] and also in the frequency and time domain [39,40]. This work seeks to evaluate the efficacy and usability of the FEM for the determination of the resonance frequency of multi-neck Helmholtz resonators.…”
Section: Introductionmentioning
confidence: 99%